Clinical InvestigationsRadiobiologically based treatment plan evaluation for prostate seed implants - Knaup, Courtney; Mavroidis, Panayiotis; Esquivel, Carlos; Baltas, Dimos; Stathakis, Sotirios; Swanson, Gregory; Papanikolaou, Nikos (Journal of Contemporary Brachytherapy, 2011)
Purpose: Accurate prostate low dose-rate brachytherapy treatment plan evaluation is important for future care decisions. Presently, an evaluation is based on dosimetric quantifiers for the tumor and organs at risk. However, these do not account for effects of varying dose-rate, tumor repopulation and other biological effects. In this work, incorporation of the biological response is used to obtain more clinically relevant treatment plan evaluation. Material and methods : Eleven patients were evaluated. Each patient received a 145 Gy implant. Iodine-125 seeds were used and the treatment plans were created on the Prowess system. Based on CT images the post-implant plan was created. In the post-plan, the tumor, urethra, bladder and rectum were contoured. The biologically effective dose was used to determine the tumor control probability and the normal tissue complication probabilities for the urethra, bladder, rectum and surrounding tissue. Results : The average tumor control probability and complication probabilities for the urethra, bladder, rectum and surrounding tissue were 99%, 29%, 0%, 12% and 6%, respectively. These measures provide a simpler means for evaluation and since they include radiobiological factors, they provide more reliable estimation of the treatment outcome. Conclusions : The goal of this work was to create more clinically relevant prostate seed-implant evaluation by incorporating radiobiological measures. This resulted in a simpler descriptor of treatment plan quality and was consistent with patient outcomes.